Penguatan Critical Thingking, Collaboration, Communication Dan Creative (4C) Pada Mata Kuliah PKn Melalui Mobile Learning Berbasis Schoology : - - Mariyani, Mariyani; Nurdiansyah, Edwin; Ramadhan, Arizky; Veronica, Maria; Galuh, Siulie (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2022)
The selection of the right learning media will help achieve high-level learning goals, collaboration, good communication and creativity in Civics courses. This study aims to determine: 1) how is the level of practicality of schoology-based mobile learning as strengthening 4C in Civics courses? and 2) what is the potential impact of schoology-based mobile learning as strengthening 4C in Civics courses. The method in this research is Research and Development (RnD). By doing 3 stages, namely preliminary studies, product development and testing. Data were collected through questionnaires, documentation and objective tests. Data analysis was carried out through quantitative descriptive analysis. The level of practicality of Schoology-based mobile learning shows that the results of material expert validation are 92.8% and media expert validation is 87.5%, which means that the Schoology-based mobile learning validation is valid. While the results of the schoology-based mobile learning trial results at the one to one stage obtained 84.5%, the small group stage 77.7% and the field evaluation stage 89.1%. At the trial stage, it is categorized as practical to use. And to find out the potential impact of schoology-based mobile learning, a pretest and posttest were carried out which obtained N.Gain 0.735, which means the potential impact of high school-based mobile learning. The existence of schoology-based mobile learning helps to achieve the 4C Civics learning objectives